Multislice computed tomography findings of omental infarction as a rare cause of acute abdominal pain - Koç, Mustafa; Serhatlioğlu, Selami (My University, 2017)
The aim of the present study was to evaluate multislice computed tomography (MSCT) findings of omental infarction, a rare cause of acute abdominal pain, together with a review of the current literature. The retrospective cross-sectional study included eighteen patients, between 2011 and 2015, who were admitted to our department with complaints of acute abdominal pain and who were subsequently diagnosed with omental infarction. Of these eleven patients, five (61%) were males and seven (39%) were females. The mean age was 48 years, ranging from 39 to 71 years. Radiologic imaging showed findings consistent with omental infarction localized to the ascending colon in six cases, descending colon in five cases, neighborhood of transverse colon in five patients, and neighborhood of the gall bladder in two patients. The size of the lesions ranged from 3 cm to 7 cm. Abdominal MSCT showing whirling pattern of vessels in the infarcted omental vessels and an oval-shaped “dirty fat ball” appearance with well-defined margins in the neighborhood of the colon. MSCT is superior to ultrasonography in the evaluation of omentum also allows rapid and accurate diagnosis of omental infarction and prevents unnecessary surgical interventions
Keywords: Genel ve Dahili Tıp; Radyoloji; Nükleer Tıp; Tıbbi Görüntüleme